Lipopolysaccharide-Induced Neuronal Activation in the Paraventricular and Dorsomedial Hypothalamus Depends on Ambient Temperature - Wanner, Samuel P. (Public Library of Science, 2013)
Systemic inflammatory response syndrome is associated with either fever or hypothermia, but the mechanisms responsible for switching from one to the other are unknown. In experimental animals, systemic inflammation is often induced by bacterial lipopolysaccharide (LPS). To identify the diencephalic and brainstem structures involved in the fever-hypothermia switch, we studied the expression of c-Fos protein, a marker of neuronal activation, in rats treated with the same high dose of LPS (0.5 mg/kg, intravenously) either in a thermoneutral (30°C) or cool (24°C) environment. At 30°C, LPS caused fever; at 24°C, the same dose caused profound hypothermia. Both fever and hypothermia were associated with the induction of c-Fos in many brain areas, including several structures of the anterior preoptic, paraventricular, lateral, and dorsal hypothalamus, the bed nucleus of the stria terminalis, the posterior pretectal nucleus, ventrolateral periaqueductal gray, lateral parabrachial nucleus, area postrema, and nucleus of the solitary tract. Every brain area studied showed a comparable response to LPS at the two different ambient temperatures used, with the exception of two areas: the dorsomedial hypothalamic nucleus (DMH), which we studied together with the adjacent dorsal hypothalamic area (DA), and the paraventricular hypothalamic nucleus (PVH). Both structures had much stronger c-Fos expression during LPS hypothermia than during fever. We propose that PVH and DMH/DA neurons are involved in a circuit, which – depending on the ambient temperature – determines whether the thermoregulatory response to bacterial LPS will be fever or hypothermia.